Efficacy of 2% Kojic Acid Containing Formulation vs Picosecond Laser for Treatment of Melasma - Naseemullah, Abdul Qayum Khan, Farooq Azam Khan, Shahzad Rashid Awan, Sarah Riaz Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Melasma is a frequently observed dermatological condition. The conventional therapies for melasma improvement established to date are mainly categorized into chemical peeling, topical agents and laser therapy. A new technique to reduce discomfort and post-laser discoloration induced by heat effects is the picosecond laser system. Objective: To find out efficacy of 2% kojic acid containing formulation vs picosecond laser for treatment of melasma Methodology: This was comparative randomized controlled study carried out at the department of dermatology Qazi Hussain Ahmad Medical Complex Nowshera and alshifa clinic and skin aesthetic, Nowshera for duration of one year from July 2020 to July 2021. Totally, 300 patients were included in the study. Each picosecond laser and kojic acid group comprise of 150 patients. All the information was recorded at the baseline and each following visit. Severity Index (MASI) score was calculated and color photographs were taken of all patients. Results: At baseline, the mean MASI scores for picosecond laser and kojic acid group was 10.5±3.5 and 11.2±4.1 respectively (p=0.31). In both the group significant improvement occur in the MASI scores at weeks 12 and week 20. In picosecond laser group, the most remarkable improvement rate (62%) was noted while in kojic acid containing formulation group the rate of improvement was 41.96%. Conclusion: Our study concludes that picosecond Laser device is an efficient and well-tolerated therapeutic option for melasma as compared to kojic acid containing formulation. Keywords: Efficacy; Kojic acid; Picosecond laser; Melasma